Exkursionsführer Schwarzwald eine Einführung in Landschaft und Vegetation mit 45 Wanderrouten ; 5 Tabellen - Wilmanns, Otti 1928-2023 (Ulmer, 2001)
Black Forest vegetation and landscape.
Keywords: Natural history -- Germany -- Black Forest; Plants -- Germany -- Black Forest; Exkursion; Kulturlandschaft; Biogeografie; Ökologie; Pflanzengesellschaft; Forêt-Noire (Allemagne, massif) - [guide]; Deutschland; Black Forest (Germany) -- Description and travel; Schwarzwald; Führer